Development of a numerically efficient approach based on coupled CFD/FEM analysis for virtual fire resistance tests—Part B: Deformation process of a steel structure. (29th April 2020) - Prieler, Rene; Gerhardter, Hannes; Landfahrer, Martin; Gaber, Christian; Schluckner, Christoph; Eichhorn‐Gruber, Markus; Schwabegger, Günther; Hochenauer, Christoph
Summary: In the present study, the structural analysis of a three‐parted steel door during a fire resistance test was examined by FEM simulation. The structural analysis is part of a coupled CFD/FEM simulation approach developed for the prediction of fire resistance tests. The basis of this follow‐up work was the calculated temperature in the test specimen from CFD to predict the thermal stresses, deformation and gap formation between the door parts. The spatial information of the temperature in the test specimen was exported. Subsequently, the thermal expansion of the door and the resulting stresses and gaps were calculated. To validate the FEM simulation, the deformation of the steel door was observed. It was found that the simulation predicted the deformation of the steel door in close accordance to the measurement. The maximum displacement was found in the centre of the construction with 141 mm, whereas the simulation predicted a value of 133 mm. In addition to the deformation of the door, also the prediction of the gap formation was validated against the flue gas leakage. The first flue gas exit occurred already after 120 seconds, which was in spatial and temporal conjunction with the maximum gap predicted in the simulation.